2004
DOI: 10.2214/ajr.182.1.1820137
|View full text |Cite
|
Sign up to set email alerts
|

MRI Diagnosis of Tears of the Hip Abductor Tendons (Gluteus Medius and Gluteus Minimus)

Abstract: MRI showed good accuracy for the diagnosis of tears of the gluteus medius and gluteus minimus tendons. The identification of an area of T2 hyperintensity superior to the greater trochanter had the highest sensitivity and specificity for tears at 73% and 95%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(177 citation statements)
references
References 8 publications
6
163
1
5
Order By: Relevance
“…The greater trochanteric pain syndrome is characterized by chronic pain and tenderness over the greater trochanter [1,2]. Notably, this syndrome can present both in patients with and without total hip arthroplasty (THA), and it is commonly caused by abductor tendon abnormalities [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater trochanteric pain syndrome is characterized by chronic pain and tenderness over the greater trochanter [1,2]. Notably, this syndrome can present both in patients with and without total hip arthroplasty (THA), and it is commonly caused by abductor tendon abnormalities [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this syndrome can present both in patients with and without total hip arthroplasty (THA), and it is commonly caused by abductor tendon abnormalities [1,[3][4][5]. In addition to severe lateral hip pain, abductor tendon tears and atrophy of the associated muscles often result in further clinical problems such as a Trendelenburg gait pattern, or immobility [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason abductor tears are under recognized is due to the difficulty in diagnosing them. Kagan et al reported no diagnostic findings on physical examination in patients with abductor tears [9] and plain radiographs are typically negative [10,11]. The Trendelenburg sign is the most sensitive and specific physical sign for the detection of gluteus medius tears [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is four times more common in women and is usually seen between the fourth and sixth decades of life [5,6]. Patients with osteoarthritis, iliotibial band tenderness, low back pain, and obesity are at an increased risk [7,8].…”
Section: Introductionmentioning
confidence: 99%